2002
DOI: 10.1097/00000539-200201000-00037
|View full text |Cite
|
Sign up to set email alerts
|

Levobupivacaine Versus Racemic Bupivacaine for Spinal Anesthesia

Abstract: Levobupivacaine, the pure S(-)-enantiomer of racemic bupivacaine is an equally effective local anesthetic for spinal anesthesia compared with racemic bupivacaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
97
2
11

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(123 citation statements)
references
References 14 publications
13
97
2
11
Order By: Relevance
“…Although plain bupivacaine 0.5% is slightly hypobaric in most patients, it is considered as isobaric in clinical practice. In Glaser et al's study [2], bupivacaine and levobupivacaine were administered intrathecally with the patients in the sitting position. In another study, Lee et al [3] administered two agents intrathecally with the patients in left lateral position.…”
Section: A Replymentioning
confidence: 99%
See 2 more Smart Citations
“…Although plain bupivacaine 0.5% is slightly hypobaric in most patients, it is considered as isobaric in clinical practice. In Glaser et al's study [2], bupivacaine and levobupivacaine were administered intrathecally with the patients in the sitting position. In another study, Lee et al [3] administered two agents intrathecally with the patients in left lateral position.…”
Section: A Replymentioning
confidence: 99%
“…They found that the racemic bupivacaine solution spread more rapidly and produced a more extensive spinal anaesthetic block with greater incidences of both hypotension and nausea, findings that do not match those of any previous worker. They discuss a number of very minor issues (age of their patients, relative potency of the drugs, and their differential vasoconstrictor action) in an attempt to explain these results, but ignore completely the two most important factors affecting intrathecal drug spread: the density of the solution and the position of the patient [2].Lumbar puncture and drug injection were performed in the sitting position and I will take much convincing to change my view that the bupivacaine solutions used were less dense than those of levobupivacaine so that they 'floated' to a greater cephalad level. This, not a difference in any inherent drug property of two very similar agents, is a much more likely explanation of their results.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[3] Levobupivacaine hydrochloride is the pure S(-)-enantiomer of racemic bupivacaine and is less toxic to the heart and central nervous system. [4,5] The present study was designed to compare the effects of racemic Bupivacaine + Fentanyl and Levobupivacaine + Fentanyl on the complete regression of motor block, onset time to reach T 10 level sensory block, duration of T 10 level sensory block, onset time of motor block, duration of sensory block (regression time to S 1 dermatome level). Exclusion criteria: Patients with serious CNS disorders, psychiatric disorders, decompensated cardiopulmonary disease, blood volume deficits, coagulopathy, peripheral neuropathies, infection at injection site, hypersensitivity to amide local anaesthetics and Fentanyl, unwilling patients were excluded from the study.…”
Section: Introductionmentioning
confidence: 99%
“…Levobupivacaine is the pure S(-) enantiomer of racemic bupivacaine. In clinical use, levobupivacaine has been shown to be equally effective as bupivacaine at comparable doses and concentrations, and has been found to produce similar anesthetic characteristics [1,8]. Furthermore, levobupivacaine has a lower risk of cardiovascular and central nervous system toxicity than bupivacaine [7].…”
Section: Introductionmentioning
confidence: 99%